THE NON-APPLICATIONS OF GOOD FAITH, TRUST, AND CONFIDENTIALITY IN ARBITRATION: A STUDY OF THE ANNULMENT CASES IN INDONESIA - Roosdiono, Anangga W.; Taqwa, Muhamad Dzadit; Salsabila, Mayta Ciara (Indonesia Law Review, 2022)
Arbitration is a dispute resolution method that is chosen by the parties for, mainly, avoiding weaknesses of resolving disputes through the general court. It has three principles, that strongly connect to one another, to hold: good faith, trust, and confidentiality. These principles determine whether a dispute resolution through arbitration will be successful. However, in many - if not all - cases, many disputing parties still do not maintain these principles. This reality can be observed in annulment cases. Although the annulment mechanism renders a protection to the parties from the errors made by intention, this mechanism opens an opportunity for these people just to pause the execution of the arbitral awards, makes their cases become open for the public, and even puts the final-and-binding status of the awards in question. On the other hand, there are still a few cases showing that such errors, made by the tribunals or the winning parties, occurred. From these cases, this paper is to question whether the existence of annulment is the key factor of the non-applications of these three principles or the tool to prevent the non-applications. First, a descriptive comprehension of these principles is elaborated. Afterwards, the annulment mechanism, provided by Article 70 of Law 30 of 1999 on Arbitration and Alternative Dispute Resolutions, is comprehended to see its nature and practical implications. At the end, some annulment cases are dissected to answer the research question.